PROBLEM BASED LEARNING DURING CONTACT AND ONLINE LEARNING - Jarulė, Virginija (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The aim of this article is to present the analysis of assessment objects – motivation, group work, assessment/self-assessment, skills formation, performed during problem-based learning in different student learning conditions. The essence of problem-based learning is to learn to solve problems by working in groups or teams, to search for information independently, to develop problem – solving strategies, to evaluate the work which was done. During a pandemic, online learning poses challenges for students to work in groups and assign tasks, as well it is more difficult to communicate and collaborate, which can make it more difficult to develop the necessary skills. Key words: problem-based learnig, PBL, contact learning, online learning.